P Pengolahan Data Keuangan Pada CV. Nagrak Perkasa Menggunakan Zahir Accounting Versi 6.0 - Nur Arafah, Alvira; Rahayu, Yuri (Program Studi Sistem Informasi Akuntansi Kampus Kota Sukabumi, 2023)
In today’s sophisticated era, all us are required to be fast-paced, effective and able to compete in the very long term in the business world. Acconting is also affected because of this increasingly sophisticated technology. As it is now, the impact has been felt, at first we still used manual recording use book, but the more sophisticated the recording has been computerized. CV. Nagrak Perkasa is a trading company engaged in the field of Specialist Wholesale of Building Materials which provides service if customers are in need of building materials. The author uses interviess, observations, and literature studies to obtain information. CV. Nagrak Perkasa still uses accounting records manually using no computerized books. Zahir Accounting Vrsion 6.0 can be a toll to record transactions an financial reports to make them more effective, efficient and accurate. Using Zahir Accounting Version 6.0 can reduce errors that occur and accounting records.